Multicolor inorganic artificial stone with textures and preparation method thereof
By using the stirring and pressing process of materials such as calcium carbonate powder, calcium carbonate sand, white silicate cement and material pigments in the production process of inorganic artificial stone, the problems of single color, high production costs and unenvironmental production process are solved, and the production of multi-color inorganic artificial stone products is realized, reducing costs, and improving environmental protection and production efficiency.
Patent Information
- Application Number
- CN202411882819.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
AI Technical Summary
The existing inorganic artificial stone products have single colors, high production costs, and unenvironmental production processes, making it difficult to meet the market's demand for diversified and personalized colors.
Textured multi-colored inorganic artificial stones are prepared by using materials such as calcium carbonate powder, calcium carbonate sand, white silicate cement and material pigment through stirring, pressing and re-adding of coloring materials. The process includes stirring evenly drying the material, hydration reaction to generate bonded material, vacuum vibration pressing and molding, and adding colored material to the surface of the material after forming, and firmly bonding the colored material with the material through re-pressing and curing.
Multi-color inorganic artificial stone products have been realized, which reduces production costs, improves production environmental protection, simplifies production processes, improves production efficiency, and meets the market's demand for diversified and personalized products.
Smart Images

Figure CN119638325A_ABST
Abstract
Description
[Technical field]
[0001] The invention relates to the technical field of artificial stones, in particular to a multi-color inorganic artificial stone with textures and a preparation method thereof. [Background technology]
[0002] As unsaturated polyester resin is the main binder of granite, due to its oily characteristics, the color powder and color paste used to produce the texture are not easily dissolved in the material during the production of granite, so various textures can be produced. However, the main binder of inorganic artificial stone is cement, and cement solidification requires the participation of water. Therefore, during the production process of inorganic artificial stone, the wettability is very strong, and the color powder and color paste are easily diluted. Therefore, there is basically no multi-color inorganic artificial stone on the market. It is mainly single-color or with glass particles and different colored aggregates for decoration.
[0003] The Chinese patent with publication number CN107471421A discloses a three-color inorganic artificial stone and a manufacturing method thereof. The manufacturing method described in the invention is to weigh all components according to weight percentage into three mixing tanks, add pigments of different colors into the three mixing tanks, and then stir and press to form. The Chinese patent with publication number CN118373641A discloses a three-color patterned inorganic artificial stone plate and a preparation process thereof. The artificial stone pattern described in the invention is formed by three-color granulation, respectively weighing coarse-grained quartz sand and fine-grained calcium sand of color A, color B and color C according to the raw material ratio, and uniformly mixing the components of each color part by stirring.
[0004] Analyzing the above two inventions, it is not difficult to find that they have some common limitations. First, the main materials used in both are mainly quartz sand, and there are cases where coarser quartz sand particles are used as a color matching element. This color comes from the inherent color of the small-size aggregate itself, rather than the color specially given by adding additional pigments. This has certain limitations in the richness and controllability of the color. Secondly, their methods of achieving multi-color effects are to simply match several materials to form multiple colors. This method is relatively traditional and lacks innovation, and it is difficult to meet the current market demand for diversified and personalized colors of artificial stones.
[0005] Furthermore, from the perspective of production and processing, although the quartz sand material has the characteristics of hard texture, this also makes its later processing difficulty significantly increased. During the processing, high-intensity noise will be generated, which not only affects the working environment, but also may cause damage to the hearing of the operator. At the same time, the silica dust produced during the production and processing process has high hardness. Once inhaled by the human body, it is easily adsorbed in the lungs and difficult to expel. Long-term accumulation will greatly increase the risk of serious diseases such as silicosis and pulmonary fibrosis, posing a great threat to the health of the operator. In addition, the general production method of the above invention is single-board production. This production mode has the disadvantages of high production cost, long production time and large site area, which greatly limits the improvement of production efficiency and economic benefits, is not conducive to the company to maintain a dominant position in the market competition, and it is difficult to meet the needs of large-scale industrial production.
[0006] The disclosure of the above background technology content is only used to assist in understanding the inventive concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application. In the absence of clear evidence that the above content has been disclosed on the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. [Summary of the invention]
[0007] The purpose of the present invention is to provide a textured multi-color inorganic artificial stone and a preparation method thereof, so as to solve the technical problems of the inorganic artificial stone in the prior art, such as single pattern and color, high production cost and environmentally unfriendly production process.
[0008] To achieve the above object, the present invention adopts the following technical solutions:
[0009] A method for preparing a textured multi-color inorganic artificial stone comprises the following steps:
[0010] (1) weighing and pouring calcium carbonate powder, calcium carbonate sand, white silicate cement and material pigment into the same stirring pot and stirring;
[0011] (2) Weighing water and additives. When the stirring in step (1) lasts for 1-3 minutes, first add the weighed water into the same stirring pot and stir for 3-5 minutes, then add the weighed additives into the same stirring pot and stir for 1-3 minutes until the mixture is evenly mixed to obtain the artificial stone material;
[0012] (3) pouring the artificial stone material mixed in step (2) into a mold, placing it in a press, evacuating and pressing;
[0013] (4) taking out materials of different shapes from the pressed artificial stone materials, and adding coloring materials on the surfaces of the taken out materials;
[0014] (5) The material with the colorant added in step (4) is put into the mold again, and placed in the press room for vacuuming, vibration pressing, and then polishing after solidification to complete the production.
[0015] Preferably, the white silicate cement in step (1) is used in an amount of 19%-22% of the artificial stone material; the calcium carbonate powder is used in an amount of 10%-18% of the artificial stone material; the calcium carbonate sand has a particle size of 80-120 mesh and is used in an amount of 35%-50% of the artificial stone material; the material pigment is an iron-based pigment and is used in an amount of 0.35%-2.0% of the artificial stone material.
[0016] Preferably, the auxiliary agent in step (2) includes one or more of a polycarboxylic acid high-performance water-reducing agent, a thickener, and an adhesive, wherein the amount of the polycarboxylic acid high-performance water-reducing agent is 1.5%-2.0% of the white silicate cement added in step (1); the thickener is hydroxypropyl methylcellulose, and the amount is 0.015%-0.03% of the artificial stone material; the adhesive is polyvinyl acetate adhesive, and the amount is 0.9%-2% of the artificial stone material.
[0017] Preferably, the amount of water used in step (2) is 5.5%-7.5% of the artificial stone material.
[0018] Preferably, the stirring frequency in steps (1) and (2) is 30-50 Hz and the speed is 40-300 r / min.
[0019] Preferably, the vacuum degree of the vacuum extraction in step (3) is 0.093-0.097 Mpa, the vibration frequency is 2500-3500 r / min, and the vibration pressing takes 25-35 s to complete the pressing.
[0020] Preferably, the colorant in step (4) comprises one of a color paste or a color powder;
[0021] The color paste comprises the following components by mass percentage: 15%-25% of silicate cement, 35%-40% of 80-100 mesh calcium carbonate sand, 0.35%-2% of iron pigment, and 25%-33% of polyvinyl acetate adhesive;
[0022] The toner comprises the following components by mass percentage: 15%-25% of silicate cement, 35%-40% of 80-100 mesh calcium carbonate sand, and 0.35%-2% of iron pigment;
[0023] The colorant is prepared by adding various components into a dispersing machine according to proportion and mixing and stirring them evenly to obtain the colorant.
[0024] Preferably, when the colorant in step (4) is a color paste, the amount of the color paste used is 1.55%-4.6% of the artificial stone material; when the color powder is used, the amount of the color powder used is 0.77%-2.3% of the artificial stone material.
[0025] Preferably, the vacuum degree of the vacuum extraction in step (5) is 0.093-0.097 Mpa, the vibration frequency is 2500-3500 r / min, and the vibration pressing takes 25-35 s to complete the pressing.
[0026] The invention also provides a multi-color inorganic artificial stone with textures prepared by the method.
[0027] The following is a detailed description of the technical principles of each step of the preparation method of the present invention:
[0028] Step (1) First, calcium carbonate powder, calcium carbonate sand, white silicate cement and material pigment are poured into the same stirring pot for stirring, which is to preliminarily and evenly mix the dry materials, ensure that various solid raw materials are evenly distributed, and lay the foundation for subsequent hydration reaction and color dispersion. If water or additives are added first, the materials will react or agglomerate prematurely, making it difficult to achieve the purpose of evenly mixing the dry materials, affecting the quality uniformity and color consistency of the final product.
[0029] Step (2) first adds water and stirs, and water and white silicate cement undergo hydration reaction to generate hydration products such as hydrated calcium silicate, which are gradually wrapped on the surface of calcium carbonate sand and filled in the gaps between the fillers, bonding the raw materials together to form a material system with certain plasticity and fluidity. As stirring proceeds, the hydration reaction of cement continues, and the performance of the material gradually stabilizes. Water is first added and stirred at a specific stirring time point because the addition of water starts the hydration reaction of cement. At this time, stirring according to the prescribed time can fully hydrate the cement and allow the material to be further mixed evenly under suitable humidity and fluidity. Adding an auxiliary agent too early may interfere with the normal hydration process of cement, while adding water too late will cause uneven stirring of the material, unable to form good plasticity and fluidity, and affect subsequent molding operations. Adding an auxiliary agent later, the polycarboxylic acid high-performance water-reducing agent is adsorbed on the surface of cement particles, and the cement particles are dispersed more evenly through electrostatic repulsion, releasing more free water, thereby improving the fluidity of the material, while reducing the amount of water used and improving the strength of the artificial stone. The thickener forms a network structure in the material, increasing the viscosity and cohesion of the material, preventing the material from being too loose, and at the same time, the water retention effect ensures that there is enough water in the cement hydration process, reducing the occurrence of cracks and improving crack resistance. The adhesive forms a continuous film in the material, enhancing the bonding force between the materials, improving the density of the board and the adhesion of the colorant.
[0030] Step (3) After the stirred material is poured into the mold, the vacuum operation uses the negative pressure principle to remove the air in the material, so that the material fills the mold more tightly, reduces the internal pores, and improves the density and strength of the artificial stone. During the vibration pressing process, the vibration causes the material particles to move relative to each other, and under the action of pressure, they are more tightly stacked and combined to form a stable structure, ensuring the shape and size accuracy of the product, while further improving the strength and integrity of the product.
[0031] After step (4) of pressing, the artificial stone material has a certain strength and shape, and the excavated material is not easy to loosen and has sufficient viscosity. After adding the colorant, the cement, calcium carbonate sand and other components in the colorant interact with the corresponding components in the material, and the pigment in the colorant is evenly distributed on the surface of the material to form a natural and beautiful color effect. The cement and calcium carbonate sand in the colorant participate in the re-solidification process of the material, so that the colorant and the material are firmly combined to ensure the stability and durability of the color. This step must be performed after the material is initially formed, because only after the material has a certain strength and shape can the colorant be guaranteed to adhere to a specific position to form a natural texture effect. If the colorant is added when the material is not formed, the colorant will move and disperse in the subsequent processing process, and the texture pattern cannot be formed but becomes a color block.
[0032] Step (5) puts the material with the colorant back into the mold, and vacuumizes and vibrates the mold again to further remove the air in the material, so that the overall structure of the artificial stone is more compact and uniform. During the vibration pressing process, the colorant is fully integrated with the material to ensure the uniformity and stability of the distribution of the colorant in the product, while improving the strength and surface flatness of the product, so that the product meets the expected quality standards and decorative effects.
[0033] The beneficial effects of the present invention compared with the prior art include:
[0034] 1.Compared with ordinary inorganic artificial stone on the market
[0035] Solve the problem of single color: Currently, the inorganic artificial stones on the market are basically single-color, or only rely on adding glass particles and aggregates of different colors for decoration. The present invention can produce inorganic artificial stones with multi-color textures, enriching the colors and patterns of the products and having huge product advantages.
[0036] Production process advantages: The unique method of pressing, excavating, sprinkling powder and spraying is adopted to avoid the problem of color powder and color paste being diluted during the production process. It not only solves the problem that inorganic artificial stone is difficult to achieve multi-color, but also can more conveniently produce more diverse multi-color inorganic artificial stone products, improve product diversity and meet the needs of different consumers.
[0037] 2. Comparison with multi-color granite
[0038] Cost: The production cost of multi-color inorganic artificial stone is lower. Compared with multi-color granite, the cost of its main binder cement (about one to two thousand per ton) is much lower than the unsaturated polyester resin used in granite (about eight to ten thousand per ton), which can effectively reduce production costs and make the product more price competitive.
[0039] Environmental protection: The production process is more environmentally friendly, reducing the adverse impact on the environment during the production process, and meeting the current requirements of environmentally friendly production.
[0040] Production process: The production process is simpler, avoiding problems such as efficiency loss and cost increase caused by complex processes, which helps to improve production efficiency, thereby providing the market with more inorganic artificial stone products and enhancing market competitiveness.
[0041] 3. Comparison with other multi-color inorganic artificial stone manufacturing methods
[0042] In terms of raw materials and color matching flexibility: the multi-color inorganic stone manufactured by patents such as application numbers CN202410467992 and CN2017108115384 mainly relies on quartz sand materials, relying on the color of coarser quartz sand particles as a color matching, and several materials need to be matched into multiple colors; while the present invention only needs one material, and by selecting different color powders and color pastes, different multi-color textures can be matched, which greatly saves costs and production time, and is more flexible and efficient in raw material utilization and color matching.
[0043] In terms of production and processing: the later processing of quartz sand materials is difficult and will produce high-intensity noise. The silicon dioxide dust generated during the processing is harmful to human health. In addition, a single-board production method is generally adopted, which has the disadvantages of high production cost, long time consumption, and large site occupation. The present invention uses cement, calcium carbonate powder, sand and other materials, and can be completely produced using fine powder and fine sand. The texture and color are more delicate, real, and beautiful. It can also be produced using the rough material method and integrated molding. The production and processing process is easy, the cost is low, the harm to the health of operators is small, and the overall production advantage is obvious.
Brief Description of the Drawings
[0044] Figure 1 This is an appearance picture of a multi-color inorganic artificial stone product with texture prepared in Example 1 of the present invention;
[0045] Figure 2 This is an appearance picture of a textured multi-color inorganic artificial stone product prepared in Example 2 of the present invention. [Specific implementation method]
[0046] The present invention will be further described in detail below in conjunction with specific implementations and with reference to the accompanying drawings. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope of the present invention and its application.
[0047] Embodiment 1:
[0048] Preparation of color paste: weigh 50 g of white silicate cement, 80 g of 100 mesh calcium carbonate sand, 4 g of iron black, and 66 g of polyvinyl acetate adhesive, and mix the components using a blender to obtain the color paste.
[0049] Step (1): weigh 1300 g of calcium carbonate powder, 4000 g of calcium carbonate sand with a particle size of 90 mesh, 1200 g of white silicate cement, 6 g of titanium dioxide, and 0.5 g of iron black, pour them into the same stirring pot, and stir at a stirring frequency of 45 Hz and a speed of 200 r / min to preliminarily mix the raw materials evenly;
[0050] Step (2): When the stirring in step (1) is continued for 3 minutes, 450 g of water is first added to the same stirring pot, and stirred at the same stirring frequency and speed for 4 minutes to fully hydrate the cement and provide the material with suitable humidity and fluidity; then 24 g of polycarboxylic acid high-performance water-reducing agent, 1.5 g of hydroxypropyl methylcellulose, and 70 g of polyvinyl acetate adhesive are added, and stirring is continued for 5 minutes until the mixture is uniformly mixed to obtain an artificial stone material;
[0051] Step (3): pour the artificial stone material mixed in step (2) into a mold, put it into a press and evacuate it to a vacuum degree of 0.095 MPa, and then vibrate and press it at a vibration frequency of 3500 r / min for 35 seconds;
[0052] Step (4): taking out materials of different shapes from the pressed artificial stone material, and adding the prepared color paste on the surface of the taken out materials;
[0053] Step (5): Put the material with colorant added in step (4) into the mold again, put it into the press room and evacuate it again to make the vacuum degree reach 0.095Mpa, then vibrate and press it at a vibration frequency of 3500r / min for 35s to complete the pressing. After waiting for the solidification to be completed, the artificial stone is polished and polished to complete the production of multi-color inorganic artificial stone with texture. Product picture see Figure 1 .
[0054] Embodiment 2:
[0055] Preparation of color powder: weigh 10g of white silicate cement, 20g of 90-mesh calcium carbonate sand, 1g of iron black, and 0.05g of iron red, and mix the components using a blender to obtain the color powder.
[0056] Step (1): weigh 1200 g of calcium carbonate powder, 3900 g of calcium carbonate sand with a particle size of 90 mesh, 1400 g of white silicate cement, 5 g of titanium dioxide, 0.2 g of iron black, and 0.05 g of iron red, and pour them into the same stirring pot, and stir at a stirring frequency of 40 Hz and a speed of 150 r / min to preliminarily mix the raw materials evenly;
[0057] Step (2): When the stirring in step (1) is continued for 2 minutes, 500 g of water is first added to the same stirring pot, and stirred at the same stirring frequency and speed for 4 minutes to fully hydrate the cement and provide the material with suitable humidity and fluidity; then 25 g of polycarboxylic acid high-performance water-reducing agent, 2 g of hydroxypropyl methylcellulose, and 65 g of polyvinyl acetate adhesive are added, and stirring is continued for 2 minutes until the mixture is uniformly mixed, thereby obtaining an artificial stone material;
[0058] Step (3): pour the artificial stone material mixed in step (2) into a mold with a length, width and height of 320 mm x 320 mm x 80 mm, put it into a press and evacuate it to a vacuum degree of 0.095 MPa, and then vibrate and press it at a vibration frequency of 3000 r / min for 30 seconds;
[0059] Step (4): taking out materials of different shapes from the pressed artificial stone material, and adding the prepared color powder on the surface of the taken out materials;
[0060] Step (5): Put the material with colorant added in step (4) into the mold again, put it into the press room and evacuate it again to make the vacuum degree reach 0.095Mpa, then vibrate and press it at a vibration frequency of 3000r / min for 30s to complete the pressing. After waiting for the solidification to be completed, the artificial stone is polished and polished to complete the production of multi-color inorganic artificial stone with texture. Figure 2 .
[0061] The multi-color inorganic artificial stones of Example 1 and Example 2 were tested for bending strength and compressive strength using the T / CSBZ011-2019 standard, and the results are shown in the table below.
[0062] Experimental groups Bending strength(MPa) Standard ground compression strength (MPa) Example 1 21.9 90 Example 2 18.5 84
[0063] Note: T / CSBZ011-2019 stipulates that the bending strength of inorganic artificial stone is ≥8MPa, and the standard ground compression strength of inorganic artificial stone is ≥50MPa.
[0064] According to the T / CSBZ011-2019 standard, the bending strength of inorganic artificial stone must reach an indicator of ≥8MPa. In this experiment, the bending strength of Example 1 was 21.9MPa, and the bending strength of Example 2 was 18.5MPa. This shows that the bending strengths of both Example 1 and Example 2 far exceed the minimum requirements specified by the standard, and can well meet the standard's specifications for bending strength, showing that these two types of multi-color inorganic artificial stones have sufficient strength protection when subjected to bending forces, and can be used in application scenarios with certain requirements for bending strength.
[0065] The T / CSBZ011-2019 standard stipulates that the standard ground compression strength of inorganic artificial stone must be ≥50MPa. The test results of this experiment show that the standard ground compression strength of Example 1 reaches 90MPa, and the standard ground compression strength of Example 2 is 84MPa. This means that the compression strength of Example 1 and Example 2 also greatly exceeds the standard requirements, indicating that these two multi-color inorganic artificial stones can show excellent compressive resistance when subjected to vertical pressure. In actual use, such as ground paving and other application scenarios, they can withstand greater pressure without being easily damaged.
[0066] Although what is considered as exemplary embodiments of the present invention has been described and described, it will be understood by those skilled in the art that various changes and substitutions may be made thereto without departing from the spirit of the present invention. In addition, many modifications may be made to adapt specific situations to the teachings of the present invention without departing from the central concept of the present invention described herein. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but the present invention may also include all embodiments and their equivalents that fall within the scope of the present invention.
Claims
1. A method for preparing a textured multi-color inorganic artificial stone, characterized in that: The following steps are involved: (1) weighing and pouring calcium carbonate powder, calcium carbonate sand, white silicate cement and material pigment into the same stirring pot and stirring; (2) Weighing water and additives. When the stirring in step (1) lasts for 1-3 minutes, first add the weighed water into the same stirring pot and stir for 3-5 minutes, then add the weighed additives into the same stirring pot and stir for 1-3 minutes until the mixture is evenly mixed to obtain the artificial stone material; (3) pouring the artificial stone material mixed in step (2) into a mold, placing it in a press, evacuating and pressing; (4) taking out materials of different shapes from the pressed artificial stone materials, and adding coloring materials on the surfaces of the taken out materials; (5) The material with the colorant added in step (4) is put into the mold again, and placed in the press room for vacuuming, vibration pressing, and then polishing after solidification to complete the production.
2. The method for preparing a textured multi-color inorganic artificial stone according to claim 1, characterized in that: The white silicate cement in step (1) is used in an amount of 19%-22% of the artificial stone material; the calcium carbonate powder is used in an amount of 10%-18% of the artificial stone material; the calcium carbonate sand has a particle size of 80-120 meshes and is used in an amount of 35%-50% of the artificial stone material; the material pigment is an iron-based pigment and is used in an amount of 0.35%-2.0% of the artificial stone material.
3. The method for preparing a textured multi-color inorganic artificial stone according to claim 1, characterized in that: The auxiliary agent in step (2) includes one or more of a polycarboxylic acid high-performance water-reducing agent, a thickener, and an adhesive. The amount of the polycarboxylic acid high-performance water-reducing agent is 1.5%-2.0% of the white silicate cement added in step (1); the thickener is hydroxypropyl methylcellulose, and the amount is 0.015%-0.03% of the artificial stone material; the adhesive is polyvinyl acetate adhesive, and the amount is 0.9%-2% of the artificial stone material.
4. The method for preparing a textured multi-color inorganic artificial stone according to claim 1, characterized in that: The amount of water used in step (2) is 5.5%-7.5% of the artificial stone material.
5. The method for preparing a textured multi-color inorganic artificial stone according to claim 1, characterized in that: The stirring frequency in steps (1) and (2) is 30-50 Hz and the speed is 40-300 r / min.
6. The method for preparing a textured multi-color inorganic artificial stone according to claim 1, characterized in that: The vacuum degree of the vacuum pumping in step (3) is 0.093-0.097Mpa, the vibration frequency is 2500-3500r / min, and the vibration pressing is completed for 25-35s.
7. The method for preparing a textured multi-color inorganic artificial stone according to claim 1, characterized in that: The colorant in step (4) includes one of a color paste or a color powder; The color paste comprises the following components by mass percentage: 15%-25% of silicate cement, 35%-40% of 80-100 mesh calcium carbonate sand, 0.35%-2% of iron pigment, and 25%-33% of polyvinyl acetate adhesive; The toner comprises the following components by mass percentage: 15%-25% of silicate cement, 35%-40% of 80-100 mesh calcium carbonate sand, and 0.35%-2% of iron pigment; The colorant is prepared by adding various components into a dispersing machine according to proportion and mixing and stirring them evenly to obtain the colorant.
8. The method for preparing a textured multi-color inorganic artificial stone according to claim 1, characterized in that: When the color material adopts color paste, the amount of the color paste is 1.55%-4.6% of the artificial stone material; when the color powder is adopted, the amount of the color powder is 0.77%-2.3% of the artificial stone material.
9. The method for preparing a textured multi-color inorganic artificial stone according to claim 1, characterized in that: The vacuum degree of the vacuum pumping in step (5) is 0.093-0.097Mpa, the vibration frequency is 2500-3500r / min, and the vibration pressing is completed for 25-35s.
10. A multi-color inorganic artificial stone with texture prepared according to the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Three-color inorganic artificial stone and manufacturing method thereof
CN107471421A
Three-color stripe inorganic artificial stone plate and preparation process thereof
CN118373641A